(untitled) (Revista Electrónica REDINE, 2022)
The present investigation was of a descriptive field, which had as objective to analyze the didactic competences of the virtual university teachers of the school of political science of the Fermín Toro University, the study population was made up of 23 virtual teachers, it was not required sample because the entire population was taken. The information was collected using a questionnaire-type instrument composed of 16 questions on a Likert scale, which was validated through the expert judgment technique. The results were presented in graphs and tables. It was concluded that university teachers have didactic planning skills, content treatment skills, methodology skills, communication skills, tutorial skills, but there are weaknesses related to the assessment of learning through instruments, for which training is recommended. in this area, as well as educating the teacher in emotional and spiritual intelligence so that they foster a critical and reflective spirit in the students.